Differences in the response of carbon assimilation to summer stress (water deficits, high light and temperature) in four Mediterranean tree species - Faria, T; Silvério, D; Breia, E; Cabral, R; Abadía, A; Abadia, J; Pereira, J S; Chaves, M M (Physiologia Plantarum, 1998)
Daily changes in photoprotective mechanisms were studied in sun leaves of Quercus suber L., Quercus ilex L., Olea europaea L. and Eucalyptus globulus Labill. trees during the summer in Portugal. Even though stomatal closure explained most of the diurnal variation in carbon assimilation along the summer, a decline in the photochemical yield of photosystem II (F′v/F′m) also occurred, as a result of an excess of intercepted solar radiation when carbon assimilation is limited by stomatal closure due to high vapour pressure deficits and/or soil water deficits. These changes were accompanied by the conversion of violaxanthin to antheraxanthin and zeaxanthin which were correlated with thermal dissipation of excess photon energy. In spite of a common general response, differences between species were observed -Olea europaea, which is a slow-growing tree, had the lowest net photosynthetic rates, the highest proportion of carotenoids in relation to chlorophyll and the highest rates of de-epoxidation of violaxanthin. This enabled a large thermal dissipation of the excess intercepted radiation but led to rather small values of light utilisation for photochemistry (ca 20%). In contrast, in E. globulus, a fast-growing tree, photosynthetic rates were the highest, thermal dissipation of absorbed radiation the lowest and maximal values of light utilisation for photochemistry reached ca 50%. The two Quercus species exhibited an intermediate response. A high degree of co-ordination is apparent between stomatal behaviour, photosynthetic capacity and photoprotection mechanisms.
Keywords: Energy dissipation; Eucalyptus globulus; Olea europaea; photosynthesis; Quercus ilex; Quercus suber; xanthophyll cycle; zeaxanthin